Exhaled Breath Temperature Home Monitoring to Detect NSCLC Relapse: Results from a Pilot Study. (21st February 2022) - Carpagnano, Giovanna Elisiana; Popov, Todor A.; Scioscia, Giulia; Ardò, Nicoletta Pia; Lacedonia, Donato; Malerba, Mario; Tondo, Pasquale; Soccio, Piera; Loizzi, Domenico; Foschino Barbaro, Maria Pia; Sollitto, Francesco
Abstract : Background . Exhaled breath temperature (EBT) has been shown to reflect airway inflammation as well as increased vascularization, both involved in the pathogenesis of lung cancer. The aim of this study was to look for evidence that continuous EBT monitoring by such a device may help the early detection of relapse of lung cancer in patients with NSCLC who have been subjected to surgery with radical intent. Case Series . We included 11 subjects, who had been subjected to lung resection with radical intent for NSCLC in a prospective observational study. All patients received individual devices for EBT measurement and used them daily for 24 months after surgery. Subjects were also followed up by means of regular standard-of-care clinical and radiologic monitoring for lung cancer at four intervals separated by 6 months (T0, T1, T2, T3, and T4). In 5 patients, relapse of lung cancer was documented by means of lung biopsies. All of them recorded an elevation of their EBT at least one-time interval (T1), corresponding to 6 months, before the relapse was diagnosed at T4. The individual EBT graphs over time differed among these patients, and their mean EBT variability increased by +4% towards the end of 24 months of monitoring. By contrast, patients without a relapse did not document an elevation of their EBT and their variability decreased by -1.4%. Conclusions . Our pilot study provided evidence that continuous EBT monitoring can help in the early detection of lung cancer relapse.